Background study on Kuala Lumpur - Mohd Nazri, Anis Husna; Abdul Rahim, Asiah; Suhaimi, Hanis Najeha; Hj Mohd Ariffin, Noor Aziah; Ismail, Megat Mohammad Aqif (KAED Universal Design Unit (KUDU), 2022)
Chapter three will be focusing on the background details of Kuala Lumpur and the interlink of Masjid Jamek Sultan Abdul Samad. This chapter will go through the history of Kuala Lumpur before the masjid was constructed and the details of the event that happened from the beginning until Kuala Lumpur became a metropolitan city.